Prevalence and factors associated with bullying among primary school children in Erbil city, Iraq - Othman, Samir (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Bullying is a common phenomenon in childhood. It can have a serious effect on well-being and education. Several international studies have revealed that bullying is a regular problem in schools. This study aimed to determine the prevalence and risk factors of bullying among primary school children in Erbil, Iraq. Methods: A school-based cross-sectional study was carried out among 400 children attending eight public primary schools from different socioeconomic statuses in Erbil city from October 2022 to February 2023. Data were collected by using a self-administered questionnaire in the local language with the researchers' direction and guidance. Results: Out of 400 students, 52.7% were males, and 41.7% were females, with a male-to-female ratio of 1.1:1. The mean ± SD of age was 11.12 ± 1.13 years, ranging from 9 - 13 years. The prevalence of bullying was (55.8%), and the most common types of bullying were verbal (39.9%) and physical (38.1%). The adjusted logistic regression analysis revealed that being male gender (OR=2.23), age > 12 years (OR=2.33), going to school on foot (OR=2.17), illiterate mothers (OR=0.29), illiterate fathers, read and write, primary school and secondary school (OR=3.58 OR=2.77, OR=4.23, and OR=2.74, respectively), families fight at home (OR=2.15), students bullied by family and or siblings at home (OR=2.58) were significantly associated with bullying behavior. Conclusion: Bullying is relatively high among primary school children in our region compared to neighboring countries. Parents and teachers should acknowledge and address such problems and encourage collaboration among professionals in the education and health sectors to understand the exceptional problems children experience and identify bullying.